Exploring men’s health in medium and high complexity care in Brazil: A deductive thematic analysis of social determinants - Márcio Soares de Almeida; Bruna Rafaela Carneiro; Albert Ramon Oliveira Santos; Claudia Geovana da Silva Pires; Fransley Lima Santos; Alvaro Francisco Lopes de Sousa; Anderson Reis de Sousa; Álvaro Pereira; Layze Braz de Oliveira; Liliane Moretti Carneiro; Isabel Amélia Costa Mendes (Belitung Nursing Journal, 2024)
Background: Men’s health is influenced by a complex interplay of social, economic, and cultural determinants. Understanding how these aspects affect the health of adult cisgender men in medium and high-complexity healthcare settings is essential for improving healthcare services and promoting better health outcomes.